Student Teaching Reform (pp. 55--57) - Thornton, Zach (Ohio Journal of School Mathematics, 2020)
The author explores problems inherent in popular models of student teaching along with poten-tial solutions that better address the needs of candidates, cooperating teachers, and university supervisors.